2000
DOI: 10.1146/annurev.genom.1.1.409
|View full text |Cite
|
Sign up to set email alerts
|

DNA Helicases, Genomic Instability, and Human Genetic Disease

Abstract: DNA helicases are a highly conserved group of enzymes that unwind DNA. They function in all processes in which access to single-stranded DNA is required, including DNA replication, DNA repair and recombination, and transcription of RNA. Defects in helicases functioning in one or more of these processes can result in characteristic human genetic disorders in which genomic instability and predisposition to cancer are common features. So far, different helicase genes have been found mutated in six such disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(172 citation statements)
references
References 209 publications
1
167
0
4
Order By: Relevance
“…Thus, cell division in adult somatic tissues appears to put organisms at risk for developing cancer. This is not surprising, given that we now know that DNA replication puts cells at endanger for acquiring and fixing mutations (Kunkel and Bebenek, 2000;van Brabant et al, 2000;Friedberg et al, 2002;Thompson and Schild, 2002), and that somatic mutations are a major cause of cancer (Bishop, 1995;Simpson and Camargo, 1998;Gray and Collins, 2000;Knudson, 2000).…”
Section: Cancer and Age-related Diseasementioning
confidence: 99%
“…Thus, cell division in adult somatic tissues appears to put organisms at risk for developing cancer. This is not surprising, given that we now know that DNA replication puts cells at endanger for acquiring and fixing mutations (Kunkel and Bebenek, 2000;van Brabant et al, 2000;Friedberg et al, 2002;Thompson and Schild, 2002), and that somatic mutations are a major cause of cancer (Bishop, 1995;Simpson and Camargo, 1998;Gray and Collins, 2000;Knudson, 2000).…”
Section: Cancer and Age-related Diseasementioning
confidence: 99%
“…82 These biochemical activities suggested that BLM might act on a replication fork that was stalled and reversed by a DNA lesion (forming a Holliday Junction; ref. 84). Following lesion repair, the BLM helicase was proposed to unwind the four-strand junction starting at the single open-end to restore a functional replication fork.…”
Section: Autosomal Recessive Predisposition To Cancermentioning
confidence: 99%
“…Defects in a variety of DNA repair pathways result in diseases characterized by a range of distinct phenotypes. For example, defects in DNA helicases (for example, Bloom syndrome) can result in dwarfism and increased sister-chromatid exchange, defects in the repair of DNA crosslinks (Fanconi anemia) is associated with diverse congenital abnormalities and bone marrow failure, while defects in the repair of UV damage (for example, xeroderma pigmentosum) can lead to sun-induced skin and eye lesions, and all of these DNA repair syndromes predispose to cancer (van Brabant et al, 2000;Hoeijmakers, 2001;D'Andrea, 2003;Cleaver, 2005). Human syndromes also result from defective responses to DNA double-strand breaks (DSBs), such as ataxia telangiectasia (AT) and Nijmegen breakage syndrome (NBS) that show striking effects in the nervous and immune systems and exhibit cancer predisposition (McKinnon and Caldecott, 2007).…”
Section: Introductionmentioning
confidence: 99%